“This is what a 13-year old girl looks like”: a feminist analysis of To Catch a Predator - Tabor, Courtney D. (Crime, media, culture, 2023)
Through archival research and an intersectional thematic analysis, this paper examines three key episodes of early-2000s sensation To Catch a Predator and situates them within crime media and journalism literature. The paper analyzes themes of journalistic integrity and the subjugation of women and girls by a television program that claimed to use the former to stop the latter. Based on the analysis, To Catch a Predator engages in forensic journalism as demonstrated by the treatment of women and girls as bait, claims of ownership over women and girls’ bodies, lack of nuance in reporting, and the liberties taken in their journalistic practices. Ultimately, this paper shows how To Catch a Predator acts as a spectacle of vigilantism, by creating the child pornography it claims to fight and by glorifying punishment, contributing to the ongoing moral panic around child exploitation.